Shear behaviour of multi-joint specimens: role of surface roughness and spacing of joints. Issue 2 (16th June 2020) - Liu, Richeng; Han, Guansheng; Jiang, Yujing; Yu, Liyuan; He, Ming
Abstract : Although many previous studies have investigated the shear behaviour of single rock joints, few of them have focused on the shear behaviour of multi-joint rock specimens under constant normal stiffness boundary conditions. This study describes the manufacture of a series of rock specimens containing multiple parallel rough joints and estimates the role of surface roughness and spacing of joints during shearing. The results show that the upper joint is crushed while the lower joint is scratched after shearing for a two-joint specimen. The middle joint is more significantly damaged/scratched than the upper and lower joints after shearing for a three-joint specimen. The joint surface roughness plays a clearer role on the variations in shear stress, normal displacement and normal stress for a three-joint specimen than that for a two-joint specimen. With the increment of shear displacement, the surface resistance index (SRI) defined as the ratio of shear stress to normal stress exhibits peak values and residual values. As the spacing of joints increases, the peak SRI generally increases at a rate in the range of 0·15–0·22/cm, except for one specimen containing three joints with a relatively rough surface.